PEMANFAATAN SISTEM INFORMASI KESEHATAN UNTUK MENINGKATKAN AKSES DAN KUALITAS LAYANAN KESEHATAN DI DESA - Toar. W. J Hatibie; Anastasia Bata; Nursela Adjim (LPPM Universitas Bina Mandiri Gorontalo, 2023)
In many villages, people still have difficulty getting adequate health services. Long distances to health facilities, lack of medical personnel, and lack of information about available services often become obstacles for people to get the care they need. In this context, SIK acts as a solution to overcome these problems by providing fast and accurate access to information. The method used in this service is to conduct an initial survey to identify health problems that commonly occur in the village. The socialization was carried out on June 5 2023 with 35 participants in Pilohayangan Village, Kab. Gorontalo. Socialization uses local media, such as village radio, posters, and community meetings to spread information. The results of this service are better health services, reduced costs, increased trust and increased community empowerment. In conclusion, health information systems are an important tool for overcoming health service challenges in villages and improving the welfare of rural communities.